Pregnancy-associated spontaneous coronary artery dissection: insights from a case series of 13 patients - Cade, Jamil Ribeiro [UNIFESP] (2017)
Aims We sought to present a series of 13 pregnancy-associated spontaneous coronary artery dissection (P-SCAD), their angiographic and multimodal imaging findings, acute phase treatment, and outcomes. Methods and results Between 2005 and 2015, 13 cases of P-SCAD were collected from a database of 11 tertiary hospitals. The mean age was 33.8 3.7 years